2022
DOI: 10.3390/ijerph191811185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Return Air Inlets’ Location on the Control of Fine Particle Transportation in a Simulated Hospital Ward

Abstract: The COVID-19 pandemic has made significant impacts on public health, including human exposure to airborne pathogens. In healthcare facilities, the locations of return air vents in ventilation systems may have important effects on lowering airborne SARS-CoV-2 transmission. This study conducted experiments to examine the influence of different return air vents’ heights (0.7 m, 1.2 m, and 1.6 m) on the particle removal effects in a simulated patient ward. Three different ventilation systems were examined: top cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…To make faster predictions, various numerical simulation models have also been proposed. A lot of work has been done both from the perspective of general modeling of aerosol spread, [6][7][8][9][10] and for making predictions in specific scenarios, ranging from hospital rooms, [11][12][13] classrooms 14 and restaurants, 15,16 to aircrafts, 17 cars 18 and buses. 19,20 We refer to References 21-23 for comprehensive reviews of different computational models for aerosol transmission.…”
Section: Introductionmentioning
confidence: 99%
“…To make faster predictions, various numerical simulation models have also been proposed. A lot of work has been done both from the perspective of general modeling of aerosol spread, [6][7][8][9][10] and for making predictions in specific scenarios, ranging from hospital rooms, [11][12][13] classrooms 14 and restaurants, 15,16 to aircrafts, 17 cars 18 and buses. 19,20 We refer to References 21-23 for comprehensive reviews of different computational models for aerosol transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The CFD approach to the study of the spread of viral particles was used to simulate the transmission of the virus in urban public places [46,47], considering different landscape designs and air speeds, in rooms with different partitions [48][49][50][51][52], risks assessment [53][54][55], and construction drainage pipes [56]. Options for optimizing ventilation and air The factors that provide a comfortable microclimate and the theoretical foundations for modeling the microclimate in cabins based on the balance equations of heat flows are presented in [1][2][3][4][5], "the processes of convective heat exchange with the environment are described" [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The CFD approach to the study of the spread of viral particles was used to simulate the transmission of the virus in urban public places [46,47], considering different landscape designs and air speeds, in rooms with different partitions [48][49][50][51][52], risks assessment [53][54][55], and construction drainage pipes [56]. Options for optimizing ventilation and air conditioning systems are considered, including the spread of a part of the virus in buildings [57], buses and trains [58,59], and in two-phase flow systems [60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of air supply temperature, relative humidity, ventilation rate and ventilation pattern on the number of aerosols suspended, deposited, and escaped droplets Villafruela et al 18 The suitability of adopting a displacement ventilation strategy in airborne infection isolation rooms Liu et al 19 In a typical two-bed ward layout, which locations have the most significant biological aerosol deposition Ren et al 20 Determine the optimal return air height under different ventilation types discovered that compared with mixing ventilation, the adoption of displacement ventilation strategy can reduce the exposure to contaminants of health worker. Recently, Kong et al 16 considered that the side return air can effectively reduce exposure of pollutants and improve the filtration efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 19 compared the cross-infection situation in a two-bed hospital ward, and the results showed that unilateral downward ventilation had better removal effect on bioaerosols than bilateral downward ventilation. Using experiments and multi-criterion analysis (i.e., the filtration effect and energy consumption), Ren et al 20 found that the optimal height of the return air vent was constant under different air supply types.…”
Section: Introductionmentioning
confidence: 99%